Flame-retardant fabric with infrared shielding performance and preparation method thereof

By using magnesium hydroxide/zinc oxide composite filler and surface-modified polyimide composite fibers in fabrics, the shortcomings of fabrics in infrared shielding and flame retardant properties are solved, and the stability and safety of fabrics are improved in high temperature environments.

CN119194709BActive Publication Date: 2025-03-14HEFEI AIJIA RADIATION PROTECTION TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411718356.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-14
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

Existing fabrics have shortcomings in infrared shielding and flame retardant properties, especially in high temperature or strong radiation environments, the infrared thermal reflectivity of the material decreases and the flame retardant efficiency is limited, resulting in limited stealth effect and safety.

Method used

Magnesium hydroxide/zinc oxide composite filler and surface-modified polyimide composite fiber are used to improve the infrared shielding, flame retardant and mechanical properties of the fabric through the synergistic effect of magnesium hydroxide nanowires and zinc oxide particles.

Benefits of technology

It significantly improves the overall performance of the fabric, including infrared shielding, flame retardant and mechanical properties, and can maintain stable performance in high temperature environments, extend service life, and improve safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194709B_ABST
    Figure CN119194709B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of functional fabrics, and provides a flame-retardant fabric with infrared shielding performance and a preparation method thereof. The fabric is prepared by a textile process from a blended yarn of a polyester composite fiber and a surface-modified polyimide composite fiber. The polyester composite fiber contains a magnesium hydroxide / zinc oxide composite filler, which is prepared by melt blending and spinning, and the surface-modified polyimide composite fiber is obtained by surface modification treatment of basic zinc carbonate. The zinc oxide particles and magnesium hydroxide nanowires in the magnesium hydroxide / zinc oxide composite filler act synergistically to enhance the flame retardancy and infrared shielding ability of the fiber; the use of surface-modified graphene improves the mechanical and thermal stability of the polyimide fiber. By reasonably regulating the fiber ratio and weaving density, the fabric has excellent mechanical properties, infrared shielding properties and flame retardant properties while ensuring flexibility, and has a wide range of application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of functional fabrics, and in particular to a flame-retardant fabric with infrared shielding performance and a preparation method thereof. Background Art

[0002] In high temperature or strong radiation environments, the protective performance of materials is crucial, especially in the fields of military, aerospace, construction, etc., where the infrared shielding and flame retardant properties of fabrics have become key requirements. Such application scenarios often involve complex environments such as extreme temperatures, strong infrared radiation, and fires. Therefore, the materials are required to not only effectively block infrared radiation to avoid detection or overheating, but also have good flame retardant properties to reduce the safety hazards caused by fires. These fabric materials must have high thermal stability, antioxidant properties, and good aging resistance on the basis of maintaining structural strength and flexibility to ensure their long service life and stable performance in harsh environments. Infrared shielding performance can not only help these fabrics achieve more efficient stealth effects in fields such as military camouflage and energy management, but also reduce the temperature of the material surface by reflecting and scattering radiant heat, thereby extending its service life. On the other hand, flame retardant properties can effectively reduce the burning speed and the release of harmful gases when a fire occurs, and enhance the safety of the material. Therefore, the development of a fabric material with both infrared shielding and flame retardant properties can not only significantly improve its protective performance in high temperature and high radiation scenarios, but also broaden its application scope in industries such as industry and firefighting, and promote the development of related industries.

[0003] At present, although the existing technology has made certain progress in the research and development of infrared shielding and flame-retardant fabrics, there are still obvious shortcomings. For example, the Chinese patent with publication number CN118048784A discloses a flame-retardant functional layer on the surface of a fabric, a preparation method thereof, and a flame-retardant fabric. Although it has basic flame-retardant functions, its infrared shielding efficiency still has a large room for improvement under high temperature or strong radiation environments, especially when exposed to high radiation for a long time, the infrared thermal reflectivity of the material gradually decreases, affecting its stealth effect. In addition, in terms of flame retardant properties, the flame retardant efficiency of existing materials in high temperature environments is limited, the pyrolysis products of the materials are prone to cause intensified combustion, and the flame retardant effect is difficult to sustain. The main reason for these problems is the lack of synergy between the materials, especially the weak dispersibility and interface bonding between the infrared shielding component and the flame retardant component, which makes it impossible to stably exert their respective properties in a high temperature environment. The existing composite material design often focuses on the improvement of a single performance, while ignoring the importance of multifunctional synergistic effects. Therefore, how to achieve the synergistic improvement of infrared shielding and flame retardant properties through surface modification and structural optimization of materials is still a key challenge in current research. Summary of the invention

[0004] (1) Technical issues solved

[0005] The purpose of the present invention is to provide a flame-retardant fabric with infrared shielding performance and a preparation method thereof, so as to solve the problem that the existing fabrics are insufficient in infrared shielding and flame-retardant performance.

[0006] (2) Technical solution

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] A flame-retardant fabric with infrared shielding performance, obtained by weaving yarns as warp yarns and weft yarns respectively, wherein the yarns are obtained by blending polyester composite fibers and surface-modified polyimide composite fibers;

[0009] The polyester composite fiber is prepared by the following components in parts by mass: 4.0 to 8.0 parts of magnesium hydroxide / zinc oxide composite filler, 50 to 90 parts of polyester chips, 0.5 to 2.5 parts of polyethylene glycol and 0.4 to 1.2 parts of phthalate;

[0010] The magnesium hydroxide / zinc oxide composite filler is composed of zinc oxide particles and magnesium hydroxide nanowires uniformly loaded on the surface of the zinc oxide particles;

[0011] The surface-modified polyimide composite fiber is prepared by surface-modifying the polyimide composite fiber with basic zinc carbonate;

[0012] The polyimide composite fiber is prepared by the following components in parts by mass: 0.5 to 3.5 parts of surface-modified graphene, 1.5 to 4.0 parts of polyethylene glycol, 40 to 60 parts of 4,4'-diaminodiphenyl ether, 36 to 54 parts of pyromellitic dianhydride, and 100 to 250 parts of N,N-dimethylformamide;

[0013] The surface-modified graphene is obtained by surface-modifying graphene oxide with dopamine.

[0014] Furthermore, the preparation method of the magnesium hydroxide / zinc oxide composite filler is as follows: in parts by weight, 20 to 45 parts of zinc oxide particles, 3.5 to 8.0 parts of magnesium chloride, 1.5 to 3.5 parts of magnesium oxide and 50 parts of deionized water are mixed evenly and added to a Teflon-lined high-pressure reactor, and the mixture is kept warm at 150 to 170° C. for 6 to 10 hours. After the reaction is completed, the white precipitate is filtered and collected, and then the white precipitate is washed with deionized water for 3 times. Then, the washed white precipitate, 3.0 to 6.0 parts of sodium hydroxide and 80 parts of anhydrous ethanol are added to a stainless steel autoclave, and the mixture is kept warm at 110 to 130° C. for 5 to 9 hours. After filtering, the solid powder is collected, and then washed with deionized water for 3 times, and finally dried in a vacuum drying oven at room temperature to constant weight to obtain the magnesium hydroxide / zinc oxide composite filler.

[0015] Furthermore, the mass ratio of the magnesium hydroxide to the zinc oxide is (5-15):(95-85).

[0016] Furthermore, the average diameter of the magnesium hydroxide nanowires is 35-70 nm, the average length is 100-350 nm, and the average particle size of the zinc oxide particles is 400-2000 nm.

[0017] Furthermore, the preparation method of the polyester composite fiber is as follows: magnesium hydroxide / zinc oxide composite filler, polyester chips, polyethylene glycol and phthalate are mixed evenly, added into a twin-screw extruder, melt blended, then extruded, and fibers were sprayed out through a spinneret, and the polyester composite fiber was obtained after cooling.

[0018] Furthermore, the screw aspect ratio of the twin-screw extruder is (25-40):1.

[0019] Furthermore, the extrusion temperature of the twin-screw extruder is 240-280°C.

[0020] The purpose of the magnesium hydroxide / zinc oxide composite filler design of the present invention is to improve the infrared shielding ability, flame retardant performance and mechanical properties of the fabric. The design of the magnesium hydroxide / zinc oxide composite filler used in the present invention is mainly used to enhance the infrared shielding ability, flame retardant performance and mechanical properties of the fabric. By uniformly loading magnesium hydroxide nanowires on the surface of zinc oxide particles, this composite filler shows good synergy in the material and can effectively improve the comprehensive performance of the fabric. Magnesium hydroxide, as a common inorganic flame retardant, has excellent thermal stability and flame retardant performance. Its nanowire structure not only increases the dispersibility in the matrix, but also further improves the flame retardant efficiency of the material through the nano effect. Zinc oxide particles not only have excellent thermal conductivity and optical properties, but also their reflection and scattering capabilities within the infrared spectrum range, which also enable the composite material to effectively shield infrared radiation, thereby improving the infrared shielding performance of the fabric. In addition, the synergistic effect of magnesium hydroxide and zinc oxide at high temperature enhances the thermal protection ability of the composite material. Magnesium hydroxide decomposes at high temperature to produce water vapor and hydroxide. This process absorbs a large amount of heat, delays the temperature rise of the material, and the generated water vapor dilutes the surrounding combustible gas, thereby improving the flame retardant performance of the material. Zinc oxide particles are stable at high temperatures, further enhancing the material's resistance to thermal shock. The combination of the two enables the material to exhibit stronger thermal protection capabilities in high-temperature scenarios such as fires. In terms of mechanical properties, the introduction of magnesium hydroxide nanowires not only improves the strength and rigidity of the material, but its high aspect ratio structure can also enhance the material's tensile resistance through the filling effect of multidimensional space. At the same time, the large specific surface area of ​​zinc oxide particles forms a strong interfacial bonding force with the polymer matrix, and this interfacial effect helps to improve the mechanical properties of the composite material. The synergistic effect of the two enables the fabric to have higher mechanical strength while maintaining flexibility, and adapt to more stringent application scenarios. In short, the present invention effectively combines the advantages of the two in infrared shielding, flame retardancy and mechanical properties through the design of magnesium hydroxide / zinc oxide composite fillers, giving the fabric excellent comprehensive performance, and through a reasonable component ratio and preparation process, ensures the synergy between the components, significantly improving the application potential of the fabric in the field of multifunctional protection.

[0021] Furthermore, the preparation method of the surface modified polyimide composite fiber is as follows: after evenly mixing 2.5 to 5.5 parts of basic zinc carbonate and 100 parts of 5wt.% sodium hydroxide solution by weight, the polyimide composite fiber is completely immersed in the mixed solution, the immersion time is 30 to 60 minutes, the immersion temperature is 60 to 80°C, and after the immersion is completed, it is washed with deionized water for 3 times, and finally dried at room temperature to completely obtain the surface modified polyimide composite fiber.

[0022] Furthermore, the preparation method of the polyimide composite fiber is as follows: surface modified graphene, polyethylene glycol and N,N-dimethylformamide are mixed and ultrasonicated for 30 to 45 minutes to obtain a uniformly dispersed suspension, then the suspension is added to a reactor, and 4,4'-diaminodiphenyl ether and isophthalic acid dianhydride are continued to be added under a nitrogen atmosphere, and a polycondensation reaction is carried out under stirring at 5 to 25°C for 10 to 15 hours. After the reaction is completed, a polyamic acid mixed solution is obtained, and after standing and vacuum degassing treatment, a solution spinning is carried out to obtain polyamic acid primary fibers, and then the polyamic acid primary fibers are subjected to thermal imidization and heat setting stretching treatment at 300 to 550°C for 30 to 60 minutes, and the polyimide composite fibers are obtained after cooling.

[0023] Furthermore, the preparation method of the surface modified graphene is as follows: in parts by weight, 0.5-2.5 parts of graphene oxide are added to 100 parts of deionized water, and after stirring evenly, 0.05-0.09 parts of dopamine are added, and then the pH is adjusted to 8.0-10.0 with ammonia water, and the reaction is continuously stirred at room temperature for 6-12 hours. After the stirring is completed, the mixed solution is centrifuged to collect the solid precipitate, and then the precipitate is washed once with deionized water, and finally dried to constant weight in a vacuum drying oven at room temperature to obtain the surface modified graphene.

[0024] Furthermore, the mass ratio of the 4,4'-diaminodiphenyl ether to pyromellitic dianhydride is 1:0.9.

[0025] The surface-modified polyimide composite fiber designed by the present invention has the following multiple purposes: through the synergistic effect of dopamine surface-modified graphene, polyethylene glycol and basic zinc carbonate, the flame retardant, infrared shielding and thermal management properties of the fiber are significantly improved. First, dopamine surface-modified graphene plays a key role in the composite material. After being modified by dopamine, graphene oxide not only retains the excellent conductivity of its two-dimensional sheet structure, but also forms a surface coating with better compatibility with the matrix through the self-polymerization of dopamine. This modification process improves the dispersibility of graphene in the polyimide matrix, allowing it to be more evenly distributed in the fiber, thereby significantly enhancing the infrared shielding effect of the material. Dopamine surface-modified graphene also has excellent flame retardant properties and can form a stable carbonized layer when subjected to high temperature, thereby blocking heat transfer and reducing the burning rate of the material. Polyethylene glycol has a dual function in this composite fiber system. First, as a good dispersant, polyethylene glycol can effectively improve the dispersion of surface-modified graphene in the composite fiber, further improving the uniformity and overall performance of the composite material. Secondly, polyethylene glycol has phase change endothermic characteristics. When the ambient temperature rises, it can absorb a large amount of heat energy to alleviate the temperature rise of the fiber, thereby improving the thermal management ability of the composite material to a certain extent. The addition of this phase change material not only enhances the thermal stability of the fiber, but also gives the material a certain temperature control function, so that it can maintain stable performance in an overheated environment. The introduction of basic zinc carbonate further improves the flame retardant properties and infrared shielding effects of the material. Under high temperature conditions, basic zinc carbonate first undergoes thermal decomposition, releasing flame-retardant gases, forming a physical barrier layer, reducing oxygen infiltration and heat transfer, thereby effectively inhibiting the occurrence of combustion. Its thermal decomposition product, zinc oxide, also exhibits excellent infrared shielding ability in the composite fiber, which can effectively reflect and scatter infrared radiation and enhance the infrared stealth performance of the material. In addition, the presence of zinc oxide also further improves the thermal stability of the fiber, making it exhibit better heat resistance and mechanical strength under high temperature conditions. In summary, the surface-modified polyimide composite fiber of the present invention successfully achieves multiple functions of flame retardancy, infrared shielding and thermal management through the synergistic effect of dopamine surface-modified graphene, polyethylene glycol and basic zinc carbonate. These components cooperate with each other, which not only enhances the overall performance of the material, but also makes the composite fiber show excellent stability and safety in high temperature environment, and has broad application prospects.

[0026] Furthermore, the average diameters of the polyimide composite fiber and the surface-modified polyimide composite fiber are 8-15 μm and 6-12 μm, respectively.

[0027] Furthermore, the mass ratio of the polyimide composite fiber to the surface-modified polyimide composite fiber in the yarn is (30~50):(70~50).

[0028] Furthermore, the warp yarn weaving density of the yarn is 30-60 yarns / cm, and the weft yarn weaving density is 25-50 yarns / cm.

[0029] The present invention adopts the design of polyimide composite fiber and surface modified polyimide composite fiber mainly to enhance the mechanical properties, infrared shielding properties and flame retardant properties of the yarn. By reasonably controlling the diameter of the fiber and the mass ratio of each component in the yarn, the present invention achieves effective improvement of multiple properties. First, the average diameters of the polyimide composite fiber and the surface modified polyimide composite fiber are 8-15 μm and 6-12 μm, respectively. The surface modified fiber with a smaller diameter not only enhances the flexibility and mechanical strength of the fiber, but also improves the uniformity of the distribution of the fiber in the yarn. This design helps to improve the overall structural stability of the yarn, so that it has better processing performance and mechanical performance during the weaving process. Secondly, the mass ratio of the polyimide composite fiber and the surface modified polyimide composite fiber in the yarn is designed to be (30-50): (70-50), and this ratio design fully considers the complementarity of the two fibers in different properties. The polyimide composite fiber itself has excellent thermal stability and flame retardant properties, while the surface modified polyimide composite fiber improves its interface bonding force and infrared shielding effect with other materials due to surface treatment. Therefore, by reasonably adjusting the ratio of the two, it is possible not only to ensure that the yarn has excellent mechanical properties, but also to significantly improve its infrared shielding and flame retardant properties. In particular, the introduction of surface-modified polyimide composite fibers enables the yarn to exhibit excellent protective effects under special environments (such as high temperature or strong radiation environments). In addition, the warp yarn spinning density of the yarn in the present invention is 30 to 60 strands / cm, and the weft yarn spinning density is 25 to 50 strands / cm. Such a spinning density design ensures the compactness and stability of the yarn structure while maintaining the flexibility of the yarn. The higher warp and weft yarn density not only enhances the mechanical strength of the yarn, but also optimizes the infrared shielding and flame retardant properties of the yarn. This is because the tighter textile structure can effectively block external heat radiation and oxygen infiltration by reducing the gaps between the fibers, thereby enhancing the protective properties of the yarn. In summary, the present invention achieves a synergistic improvement in mechanical properties, infrared shielding properties and flame retardant properties of the yarn by controlling the diameter of polyimide composite fibers and surface-modified polyimide composite fibers, designing the mass ratio, and optimizing the yarn spinning density. The interaction between the various components enables the yarn of the present invention to have good comprehensive performance and to meet the use requirements in application scenarios with high strength and high protection requirements.

[0030] The present invention also provides a method for preparing a flame-retardant fabric with infrared shielding performance, comprising the following steps:

[0031] S1. Preparation of fibers: According to a formula, polyester composite fibers and surface-modified polyimide composite fibers are prepared respectively, wherein the polyester composite fibers are prepared by melt-blending magnesium hydroxide / zinc oxide composite fillers, polyester chips, polyethylene glycol and phthalate and then extruding and spinning, and the surface-modified polyimide composite fibers are prepared by subjecting the polyimide composite fibers to surface modification treatment with basic zinc carbonate.

[0032] S2. Preparation of yarn: The polyester composite fiber prepared in S1 and the surface-modified polyimide composite fiber are blended according to a mass ratio, and the blended fibers are spun into yarn using conventional spinning equipment.

[0033] S3. Preparing fabric: using the yarns prepared in S2 as warp yarns and weft yarns respectively, and preparing fabric through a weaving process according to the weaving density.

[0034] S4. Packaging and storage: The fabric prepared in S3 is cut, rolled and packaged. The packaged fabric is stored in a dry and ventilated environment, avoiding direct sunlight and moisture to ensure stable fabric performance.

[0035] (3) Beneficial technical effects

[0036] 1. The present invention significantly improves the infrared shielding, flame retardancy and mechanical properties of the fabric through the design of magnesium hydroxide / zinc oxide composite filler, which has obvious advantages over the prior art. The synergistic effect of magnesium hydroxide nanowires and zinc oxide particles achieves stronger thermal protection and flame retardancy under high temperature conditions, and the infrared reflection and scattering properties of zinc oxide further enhance the radiation protection ability of the fabric. The nanostructure of magnesium hydroxide improves the dispersibility and tensile strength of the material, while zinc oxide improves the mechanical strength of the composite material through strong interface bonding with the matrix. The two show excellent synergy through reasonable component ratio and process optimization, so that the fabric still has excellent comprehensive performance under extreme environments, expanding its application potential in the field of multifunctional protection.

[0037] 2. The present invention significantly improves the comprehensive performance of polyimide composite fibers in flame retardancy, infrared shielding and thermal management through the synergistic effect of dopamine surface-modified graphene, polyethylene glycol and basic zinc carbonate. Compared with the prior art, dopamine-modified graphene not only improves the dispersibility of graphene, but also improves the infrared shielding effect and flame retardant properties of the material. Polyethylene glycol, as a dispersant and phase change material, enhances the uniformity and thermal management capabilities of the fiber, ensuring that it maintains stable performance under high temperature environments. Basic zinc carbonate releases flame-retardant gases through thermal decomposition, further enhancing the flame retardant effect of the fiber, and enhances the infrared stealth capability of the material through the infrared reflection effect of the decomposition product zinc oxide. The reasonable ratio of each component and process optimization ensure the synergistic effect, so that the material shows excellent application prospects in the fields of high temperature protection and thermal stealth.

[0038] 3. The present invention significantly improves the mechanical properties, infrared shielding properties and flame retardant properties of the yarn by precisely designing the diameter control, mass ratio and yarn spinning density of the polyimide composite fiber and the surface-modified polyimide composite fiber. Compared with the prior art, the innovation of the present invention lies in the introduction of surface-modified fibers, which enhances the flexibility and distribution uniformity of the fibers, while improving the interfacial bonding force with the matrix, thereby achieving better comprehensive performance. The yarn exhibits excellent protective effects in high temperature or strong radiation environments, solving the problem of insufficient mechanical strength and protective performance of traditional fibers in extreme environments. The reasonable ratio of fiber diameter, mass ratio and spinning density ensures the stability and safety of the fiber in high temperature scenarios, giving it a wide range of application potential in the field of high-intensity protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is the SEM scanning electron microscope morphology of the zinc oxide particles prepared in Example 1 of the present invention.

[0040] Figure 2 This is the XRD phase analysis spectrum of the zinc oxide particles prepared in Example 1 of the present invention.

[0041] Figure 3 This is the SEM scanning electron microscope morphology of the magnesium hydroxide / zinc oxide composite filler prepared in Example 1 of the present invention.

[0042] Figure 4 This is the XRD phase analysis spectrum of the magnesium hydroxide / zinc oxide composite filler prepared in Example 1 of the present invention.

[0043] Figure 5 This is a morphology picture of the flame-retardant fabric with infrared shielding properties prepared in Example 4 of the present invention. DETAILED DESCRIPTION

[0044] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0045] In the case of not specifying specific conditions, the operation in the embodiment is carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not indicated, are all common products on the market. The parts not mentioned in the technical content of the present invention will be processed with reference to the prior art. Unless otherwise specified, the following examples and comparative examples will be tested in parallel and use the same processing steps and parameters. Table 1 shows the reagents required for the examples and comparative examples and the corresponding purchasing companies.

[0046] Table 1 Reagents required for the examples and comparative examples and the corresponding purchasing companies

[0047] Example 1

[0048] A flame-retardant fabric with infrared shielding performance, obtained by weaving yarns as warp yarns and weft yarns respectively, wherein the yarns are obtained by blending polyester composite fibers and surface-modified polyimide composite fibers;

[0049] The polyester composite fiber of this embodiment is prepared from the following components in parts by mass: 4.0 parts of magnesium hydroxide / zinc oxide composite filler, 50 parts of polyester chips, 0.5 parts of polyethylene glycol and 0.4 parts of phthalate;

[0050] The magnesium hydroxide / zinc oxide composite filler of this embodiment is composed of zinc oxide particles and magnesium hydroxide nanowires uniformly loaded on the surface of the zinc oxide particles; the surface-modified polyimide composite fiber is prepared by surface-modifying the polyimide composite fiber with basic zinc carbonate;

[0051] The polyimide composite fiber of this embodiment is prepared from the following components in parts by mass: 0.5 parts of surface-modified graphene, 1.5 parts of polyethylene glycol, 40 parts of 4,4'-diaminodiphenyl ether, 36 parts of pyromellitic dianhydride, and 100 parts of N,N-dimethylformamide;

[0052] The surface-modified graphene in this embodiment is obtained by surface-modifying graphene oxide with dopamine.

[0053] The preparation method of the magnesium hydroxide / zinc oxide composite filler of the present embodiment is as follows: by weight, 20 parts of zinc oxide particles, 3.5 parts of magnesium chloride, 1.5 parts of magnesium oxide and 50 parts of deionized water are mixed evenly and added to a Teflon-lined autoclave, and kept warm at 150°C for 6 hours. After the reaction is completed, the white precipitate is filtered and collected, and then the white precipitate is washed 3 times with deionized water, and then the washed white precipitate is added to a stainless steel autoclave with 3.0 parts of sodium hydroxide and 80 parts of anhydrous ethanol, and kept warm at 110°C for 5 hours, and solid powder is collected after filtering, and then washed 3 times with deionized water, and finally dried in a vacuum drying oven at room temperature to constant weight to obtain a magnesium hydroxide / zinc oxide composite filler. The mass ratio of magnesium hydroxide to zinc oxide is 5:95. The average diameter of the magnesium hydroxide nanowires is 35nm, the average length is 100nm, and the average particle size of the zinc oxide particles is 400nm.

[0054] The preparation method of the polyester composite fiber of this embodiment is as follows: magnesium hydroxide / zinc oxide composite filler, polyester chips, polyethylene glycol and phthalate are mixed uniformly, added into a twin-screw extruder, melt blended, then extruded, and fibers are ejected through a spinneret, and the polyester composite fiber is obtained after cooling. The screw length-diameter ratio of the twin-screw extruder is 25:1. The extrusion temperature of the twin-screw extruder is 240°C.

[0055] The preparation method of the surface modified polyimide composite fiber of this embodiment is as follows: after evenly mixing 2.5 parts of basic zinc carbonate and 100 parts of 5wt.% sodium hydroxide solution by weight, the polyimide composite fiber is completely immersed in the mixed solution, the immersion time is 30 minutes, the immersion temperature is 60°C, and after the immersion is completed, it is washed with deionized water for 3 times, and finally dried at room temperature to completely obtain the surface modified polyimide composite fiber. The preparation method of polyimide composite fiber is as follows: surface modified graphene, polyethylene glycol and N,N-dimethylformamide are mixed and ultrasonicated for 30 minutes to obtain a uniformly dispersed suspension, then the suspension is added to a reactor, and 4,4'-diaminodiphenyl ether and isophthalic acid dianhydride are continued to be added under a nitrogen atmosphere, and the polycondensation reaction is carried out under stirring at 5°C for 10 hours. After the reaction is completed, a polyamic acid mixed solution is obtained, and the solution is spun after standing and vacuum degassing treatment to obtain polyamic acid primary fibers, and then the polyamic acid primary fibers are subjected to thermal imidization and heat setting stretching treatment at 300°C for 30 minutes, and the polyimide composite fibers are obtained after cooling. The preparation method of surface modified graphene is as follows: in parts by weight, 0.5 parts of graphene oxide are added to 100 parts of deionized water, and after stirring evenly, 0.05 parts of dopamine are added, and then the pH is adjusted to 8.0 with ammonia water, and the reaction is continuously stirred at room temperature for 6 hours. After stirring, the mixed solution is centrifuged to collect the solid precipitate, and then the precipitate is washed once with deionized water, and finally dried to constant weight in a vacuum drying oven at room temperature to obtain surface modified graphene.

[0056] The average diameters of the polyimide composite fiber and the surface-modified polyimide composite fiber of this embodiment are 8 μm and 6 μm, respectively. The mass ratio of the polyimide composite fiber and the surface-modified polyimide composite fiber in the yarn is 30:70. The warp yarn weaving density of the yarn is 30 yarns / cm, and the weft yarn weaving density is 25 yarns / cm.

[0057] This embodiment also provides a method for preparing a flame-retardant fabric with infrared shielding performance, comprising the following steps:

[0058] S1. Preparation of fibers: According to a formula, polyester composite fibers and surface-modified polyimide composite fibers are prepared respectively, wherein the polyester composite fibers are prepared by melt-blending magnesium hydroxide / zinc oxide composite fillers, polyester chips, polyethylene glycol and phthalate and then extruding and spinning, and the surface-modified polyimide composite fibers are prepared by subjecting the polyimide composite fibers to surface modification treatment with basic zinc carbonate.

[0059] S2. Preparation of yarn: The polyester composite fiber prepared in S1 and the surface-modified polyimide composite fiber are blended according to a mass ratio, and the blended fibers are spun into yarn using conventional spinning equipment.

[0060] S3. Preparing fabric: using the yarns prepared in S2 as warp yarns and weft yarns respectively, and preparing fabric through a weaving process according to the weaving density.

[0061] S4. Packaging and storage: The fabric prepared in S3 is cut, rolled and packaged. The packaged fabric is stored in a dry and ventilated environment, avoiding direct sunlight and moisture to ensure stable fabric performance.

[0062] according to Figure 1 As shown, the zinc oxide particles of Example 1 of the present invention are observed by SEM scanning electron microscope, and the obvious particle morphology can be clearly seen, which further proves the morphology of the zinc oxide particles. Figure 2 The XRD phase analysis spectrum of the zinc oxide particles prepared in Example 1 shows that the obtained zinc oxide has a typical crystalline phase, which further confirms the purity and crystal structure of the zinc oxide. Figure 3 The SEM morphology of the magnesium hydroxide / zinc oxide composite filler prepared in Example 1 of the present invention is shown, proving that the composite filler is composed of zinc oxide particles and magnesium hydroxide nanowires uniformly loaded on the surface thereof, and has a uniform structure and is tightly combined. Figure 4 The XRD phase analysis spectrum of the composite filler further verifies the phase characteristics of zinc oxide and magnesium hydroxide in the composite filler, indicating that the material composition is clear. Figure 5 The morphology of the flame-retardant fabric with infrared shielding performance prepared in Example 4 of the present invention proves that the flame-retardant fabric is woven by yarn as warp and weft yarn, and has good infrared shielding and flame-retardant properties, meeting the expected functional requirements. It can be concluded that the present invention successfully prepared a flame-retardant fabric with infrared shielding function by optimizing the preparation process, and the morphology and phase of the related zinc oxide particles and their composite materials have been effectively verified. Example 2

[0063] A flame-retardant fabric with infrared shielding performance, obtained by weaving yarns as warp yarns and weft yarns respectively, wherein the yarns are obtained by blending polyester composite fibers and surface-modified polyimide composite fibers;

[0064] The polyester composite fiber of this embodiment is prepared from the following components in parts by mass: 6.2 parts of magnesium hydroxide / zinc oxide composite filler, 65 parts of polyester chips, 1.1 parts of polyethylene glycol and 0.7 parts of phthalate;

[0065] The magnesium hydroxide / zinc oxide composite filler of this embodiment is composed of zinc oxide particles and magnesium hydroxide nanowires uniformly loaded on the surface of the zinc oxide particles; the surface-modified polyimide composite fiber is prepared by surface-modifying the polyimide composite fiber with basic zinc carbonate;

[0066] The polyimide composite fiber of this embodiment is prepared from the following components in parts by mass: 1.4 parts of surface-modified graphene, 2.3 parts of polyethylene glycol, 46.7 parts of 4,4'-diaminodiphenyl ether, 42 parts of pyromellitic dianhydride, and 160 parts of N,N-dimethylformamide;

[0067] The surface-modified graphene in this embodiment is obtained by surface-modifying graphene oxide with dopamine.

[0068] The preparation method of the magnesium hydroxide / zinc oxide composite filler of the present embodiment is as follows: by weight, 28 parts of zinc oxide particles, 5.1 parts of magnesium chloride, 2.1 parts of magnesium oxide and 50 parts of deionized water are mixed evenly and added to a Teflon-lined autoclave, and kept warm at 156°C for 7 hours. After the reaction is completed, the white precipitate is filtered and collected, and then the white precipitate is washed 3 times with deionized water, and then the washed white precipitate is added to a stainless steel autoclave with 4.2 parts of sodium hydroxide and 80 parts of anhydrous ethanol, and kept warm at 116°C for 7 hours, and the solid powder is collected after filtering, and then washed 3 times with deionized water, and finally dried in a vacuum drying oven at room temperature to constant weight to obtain a magnesium hydroxide / zinc oxide composite filler. The mass ratio of magnesium hydroxide to zinc oxide is 8:92. The average diameter of the magnesium hydroxide nanowires is 46nm, the average length is 175nm, and the average particle size of the zinc oxide particles is 880nm.

[0069] The preparation method of the polyester composite fiber of this embodiment is as follows: magnesium hydroxide / zinc oxide composite filler, polyester chips, polyethylene glycol and phthalate are mixed uniformly, added into a twin-screw extruder, melt blended, then extruded, and fibers are ejected through a spinneret, and the polyester composite fiber is obtained after cooling. The screw length-diameter ratio of the twin-screw extruder is 31:1. The extrusion temperature of the twin-screw extruder is 252°C.

[0070] The preparation method of the surface modified polyimide composite fiber of this embodiment is as follows: after evenly mixing 3.4 parts of basic zinc carbonate and 100 parts of 5wt.% sodium hydroxide solution by weight, the polyimide composite fiber is completely immersed in the mixed solution. The immersion time is 39 minutes and the immersion temperature is 66°C. After the immersion is completed, it is washed with deionized water for 3 times and finally dried at room temperature to completely obtain the surface modified polyimide composite fiber. The preparation method of polyimide composite fiber is as follows: surface modified graphene, polyethylene glycol and N,N-dimethylformamide are mixed and ultrasonicated for 34 minutes to obtain a uniformly dispersed suspension, then the suspension is added to a reactor, and 4,4'-diaminodiphenyl ether and isophthalic acid dianhydride are continued to be added under a nitrogen atmosphere, and the polycondensation reaction is carried out by stirring at 11°C for 12 hours. After the reaction is completed, a polyamic acid mixed solution is obtained, and the solution is spun after standing and vacuum degassing treatment to obtain polyamic acid primary fibers, and then the polyamic acid primary fibers are subjected to thermal imidization and heat setting stretching treatment at 364°C for 40 minutes, and the polyimide composite fibers are obtained after cooling. The preparation method of surface modified graphene is as follows: in parts by weight, 1.1 parts of graphene oxide are added to 100 parts of deionized water, and after stirring evenly, 0.07 parts of dopamine are added, and then the pH is adjusted to 9.0 with ammonia water, and the reaction is continuously stirred at room temperature for 8 hours. After stirring, the mixed solution is centrifuged to collect the solid precipitate, and then the precipitate is washed once with deionized water, and finally dried to constant weight in a vacuum drying oven at room temperature to obtain surface modified graphene.

[0071] The average diameters of the polyimide composite fiber and the surface-modified polyimide composite fiber of this embodiment are 10 μm and 8 μm, respectively. The mass ratio of the polyimide composite fiber and the surface-modified polyimide composite fiber in the yarn is 39:61. The warp yarn weaving density of the yarn is 36 yarns / cm, and the weft yarn weaving density is 32 yarns / cm.

[0072] This embodiment also provides a method for preparing a flame-retardant fabric with infrared shielding properties, which is the same as that in Embodiment 1 and will not be repeated here. Example 3

[0073] A flame-retardant fabric with infrared shielding performance, obtained by weaving yarns as warp yarns and weft yarns respectively, wherein the yarns are obtained by blending polyester composite fibers and surface-modified polyimide composite fibers;

[0074] The polyester composite fiber of this embodiment is prepared from the following components in parts by mass: 6.4 parts of magnesium hydroxide / zinc oxide composite filler, 74 parts of polyester chips, 1.6 parts of polyethylene glycol and 1.0 parts of phthalate;

[0075] The magnesium hydroxide / zinc oxide composite filler of this embodiment is composed of zinc oxide particles and magnesium hydroxide nanowires uniformly loaded on the surface of the zinc oxide particles; the surface-modified polyimide composite fiber is prepared by surface-modifying the polyimide composite fiber with basic zinc carbonate;

[0076] The polyimide composite fiber of this embodiment is prepared from the following components in parts by mass: 2.3 parts of surface-modified graphene, 3.1 parts of polyethylene glycol, 50 parts of 4,4'-diaminodiphenyl ether, 45 parts of pyromellitic dianhydride, and 190 parts of N,N-dimethylformamide;

[0077] The surface-modified graphene in this embodiment is obtained by surface-modifying graphene oxide with dopamine.

[0078] The preparation method of the magnesium hydroxide / zinc oxide composite filler of the present embodiment is as follows: by weight, 37 parts of zinc oxide particles, 6.2 parts of magnesium chloride, 2.6 parts of magnesium oxide and 50 parts of deionized water are mixed evenly and added to a Teflon-lined autoclave, and kept warm at 162°C for 8 hours. After the reaction is completed, the white precipitate is filtered and collected, and then the white precipitate is washed 3 times with deionized water, and then the washed white precipitate is added to a stainless steel autoclave with 4.8 parts of sodium hydroxide and 80 parts of anhydrous ethanol, and kept warm at 122°C for 7 hours, and the solid powder is collected after filtering, and then washed 3 times with deionized water, and finally dried in a vacuum drying oven at room temperature to constant weight to obtain a magnesium hydroxide / zinc oxide composite filler. The mass ratio of magnesium hydroxide to zinc oxide is 11:89. The average diameter of the magnesium hydroxide nanowires is 56nm, the average length is 250nm, and the average particle size of the zinc oxide particles is 1360nm.

[0079] The preparation method of the polyester composite fiber of this embodiment is as follows: magnesium hydroxide / zinc oxide composite filler, polyester chips, polyethylene glycol and phthalate are mixed uniformly, added into a twin-screw extruder, melt blended, then extruded, and fibers are ejected through a spinneret, and the polyester composite fiber is obtained after cooling. The screw length-diameter ratio of the twin-screw extruder is 34:1. The extrusion temperature of the twin-screw extruder is 264°C.

[0080] The preparation method of the surface modified polyimide composite fiber of this embodiment is as follows: after evenly mixing 4.4 parts of basic zinc carbonate and 100 parts of 5wt.% sodium hydroxide solution by weight, the polyimide composite fiber is completely immersed in the mixed solution. The immersion time is 48 minutes and the immersion temperature is 74°C. After the immersion is completed, it is washed with deionized water for 3 times and finally dried at room temperature to completely obtain the surface modified polyimide composite fiber. The preparation method of polyimide composite fiber is as follows: surface modified graphene, polyethylene glycol and N,N-dimethylformamide are mixed and ultrasonicated for 42 minutes to obtain a uniformly dispersed suspension, then the suspension is added to a reactor, and 4,4'-diaminodiphenyl ether and isophthalic acid dianhydride are continued to be added under a nitrogen atmosphere, and the polycondensation reaction is carried out under stirring at 19°C for 14 hours. After the reaction is completed, a polyamic acid mixed solution is obtained, and the solution is spun after standing and vacuum degassing treatment to obtain polyamic acid primary fibers, and then the polyamic acid primary fibers are subjected to thermal imidization and heat setting stretching treatment at 478°C for 51 minutes, and the polyimide composite fibers are obtained after cooling. The preparation method of surface modified graphene is as follows: in parts by weight, 1.9 parts of graphene oxide are added to 100 parts of deionized water, and after stirring evenly, 0.08 parts of dopamine are added, and then the pH is adjusted to 9.2 with ammonia water, and the reaction is continuously stirred at room temperature for 10 hours. After stirring, the mixed solution is centrifuged to collect the solid precipitate, and then the precipitate is washed once with deionized water, and finally dried to constant weight in a vacuum drying oven at room temperature to obtain surface modified graphene.

[0081] The average diameters of the polyimide composite fiber and the surface-modified polyimide composite fiber of this embodiment are 13 μm and 10 μm, respectively. The mass ratio of the polyimide composite fiber and the surface-modified polyimide composite fiber in the yarn is 44:56. The warp yarn weaving density of the yarn is 48 yarns / cm, and the weft yarn weaving density is 43 yarns / cm.

[0082] This embodiment also provides a method for preparing a flame-retardant fabric with infrared shielding properties, which is the same as that in Embodiment 1 and will not be repeated here. Example 4

[0083] A flame-retardant fabric with infrared shielding performance, obtained by weaving yarns as warp yarns and weft yarns respectively, wherein the yarns are obtained by blending polyester composite fibers and surface-modified polyimide composite fibers;

[0084] The polyester composite fiber of this embodiment is prepared from the following components in parts by mass: 8.0 parts of magnesium hydroxide / zinc oxide composite filler, 90 parts of polyester chips, 2.5 parts of polyethylene glycol and 1.2 parts of phthalate;

[0085] The magnesium hydroxide / zinc oxide composite filler of this embodiment is composed of zinc oxide particles and magnesium hydroxide nanowires uniformly loaded on the surface of the zinc oxide particles; the surface-modified polyimide composite fiber is prepared by surface-modifying the polyimide composite fiber with basic zinc carbonate;

[0086] The polyimide composite fiber of this embodiment is prepared from the following components in parts by mass: 3.5 parts of surface-modified graphene, 4.0 parts of polyethylene glycol, 60 parts of 4,4'-diaminodiphenyl ether, 54 parts of pyromellitic dianhydride, and 250 parts of N,N-dimethylformamide;

[0087] The surface-modified graphene in this embodiment is obtained by surface-modifying graphene oxide with dopamine.

[0088] The preparation method of the magnesium hydroxide / zinc oxide composite filler of the present embodiment is as follows: by weight, 45 parts of zinc oxide particles, 8.0 parts of magnesium chloride, 3.5 parts of magnesium oxide and 50 parts of deionized water are mixed evenly and added to a Teflon-lined autoclave, and kept warm at 170°C for 10 hours. After the reaction is completed, the white precipitate is filtered and collected, and then the white precipitate is washed 3 times with deionized water, and then the washed white precipitate is added to a stainless steel autoclave with 6.0 parts of sodium hydroxide and 80 parts of anhydrous ethanol, and kept warm at 130°C for 9 hours, and the solid powder is collected after filtering, and then washed 3 times with deionized water, and finally dried in a vacuum drying oven at room temperature to constant weight to obtain a magnesium hydroxide / zinc oxide composite filler. The mass ratio of magnesium hydroxide to zinc oxide is 15:85. The average diameter of the magnesium hydroxide nanowires is 70nm, the average length is 350nm, and the average particle size of the zinc oxide particles is 2000nm.

[0089] The preparation method of the polyester composite fiber of this embodiment is as follows: magnesium hydroxide / zinc oxide composite filler, polyester chips, polyethylene glycol and phthalate are mixed uniformly, added into a twin-screw extruder, melt blended, then extruded, and fibers are ejected through a spinneret, and the polyester composite fiber is obtained after cooling. The screw length-diameter ratio of the twin-screw extruder is 40:1. The extrusion temperature of the twin-screw extruder is 280°C.

[0090] The preparation method of the surface modified polyimide composite fiber of this embodiment is as follows: after evenly mixing 5.5 parts of basic zinc carbonate and 100 parts of 5wt.% sodium hydroxide solution by weight, the polyimide composite fiber is completely immersed in the mixed solution, the immersion time is 60 minutes, the immersion temperature is 80°C, and after the immersion is completed, it is washed with deionized water for 3 times, and finally dried at room temperature to completely obtain the surface modified polyimide composite fiber. The preparation method of polyimide composite fiber is as follows: surface modified graphene, polyethylene glycol and N,N-dimethylformamide are mixed and ultrasonicated for 45 minutes to obtain a uniformly dispersed suspension, then the suspension is added to a reactor, and 4,4'-diaminodiphenyl ether and isophthalic acid dianhydride are continued to be added under a nitrogen atmosphere, and the polycondensation reaction is carried out under stirring at 25°C for 15 hours. After the reaction is completed, a polyamic acid mixed solution is obtained, and the solution is spun after standing and vacuum degassing treatment to obtain polyamic acid primary fibers, and then the polyamic acid primary fibers are subjected to thermal imidization and heat setting stretching treatment at 550°C for 60 minutes, and the polyimide composite fibers are obtained after cooling. The preparation method of surface modified graphene is as follows: in parts by weight, 2.5 parts of graphene oxide are added to 100 parts of deionized water, and after stirring evenly, 0.09 parts of dopamine are added, and then the pH is adjusted to 10.0 with ammonia water, and the reaction is continuously stirred at room temperature for 12 hours. After stirring, the mixed solution is centrifuged to collect the solid precipitate, and then the precipitate is washed once with deionized water, and finally dried to constant weight in a vacuum drying oven at room temperature to obtain surface modified graphene.

[0091] The average diameters of the polyimide composite fiber and the surface-modified polyimide composite fiber of this embodiment are 15 μm and 12 μm, respectively. The mass ratio of the polyimide composite fiber and the surface-modified polyimide composite fiber in the yarn is 50:50. The warp yarn weaving density of the yarn is 60 yarns / cm, and the weft yarn weaving density is 50 yarns / cm.

[0092] This embodiment also provides a method for preparing a flame-retardant fabric with infrared shielding properties, which is the same as that in Embodiment 1 and will not be repeated here.

[0093] Comparative Example 1

[0094] The method is basically the same as Example 1, except that magnesium hydroxide nanowires are not prepared on the surface of zinc oxide particles, but an equal amount of zinc oxide particles are used to replace the magnesium hydroxide / zinc oxide composite filler.

[0095] Comparative Example 2

[0096] The invention is basically the same as Example 1, except that magnesium hydroxide powder is used instead of magnesium hydroxide nanowires, and the magnesium hydroxide powder is purchased from Jiangsu Zehui Magnesium-based New Material Technology Co., Ltd., and the mass fractions of magnesium hydroxide and zinc oxide added are the same as the mass fractions of magnesium hydroxide and zinc oxide in the magnesium hydroxide / zinc oxide composite filler.

[0097] Comparative Example 3

[0098] It is basically the same as Example 1, except that the surface of the polyimide composite fiber has not been surface-modified by basic zinc carbonate.

[0099] Comparative Example 4

[0100] The method is basically the same as Example 1, except that the graphene oxide used in the preparation of the polyimide composite fiber is surface-modified with dopamine.

[0101] Comparative Example 5

[0102] The method is basically the same as Example 1, except that polyethylene glycol is not added in the preparation of the polyimide composite fiber.

[0103] Performance Testing:

[0104] Mechanical properties: The mechanical properties test adopts the tensile properties test. According to the GB / T3923.1-2013 standard, 15 samples with a size of 200mm×50mm were taken in the warp and weft directions respectively during the test, and the tensile speed was 100mm / min for testing. The tensile strength and elongation of the fabric were recorded during the test as the basis for evaluating the mechanical properties.

[0105] Flame retardant properties: Flame retardant properties tests, including limiting oxygen index test (LOI) and vertical burning test (UL-94). The limiting oxygen index test is conducted according to GB / T5454-1997 standard. The test sample size is 150mm×58mm. 15 samples are prepared from the warp and weft directions respectively. The JF-3 oxygen index meter produced by China Jiangning Analyzer Co., Ltd. is used. During the test, the fabric sample is placed in an upwardly released nitrogen and oxygen mixed airflow to determine the minimum oxygen volume percentage required to support the combustion of the sample. The test results are considered valid only when 40%-60% of the samples meet the conditions specified in the standard.

[0106] Infrared shielding performance: The infrared shielding performance of the fabric was tested using a Fluke TislO infrared thermal imager to measure the emissivity of the fabric at 160°C.

[0107] The properties of the fabrics of Examples 1 to 4 and Comparative Examples 1 to 5 are summarized in Table 2.

[0108] Table 2 Performance summary of fabrics of Examples 1 to 4 and Comparative Examples 1 to 5

[0109]

[0110] The main difference between Comparative Example 1 and Example 1 is that, in Comparative Example 1, magnesium hydroxide nanowires are not prepared, but an equal amount of zinc oxide particles are used to replace the magnesium hydroxide / zinc oxide composite filler. As can be seen from Table 2, the composite filler containing magnesium hydroxide nanowires in Example 1 can significantly improve the tensile strength, elongation and flame retardant properties (LOI) of the fabric, because magnesium hydroxide nanowires have excellent reinforcing and flame retardant effects, while zinc oxide particles alone cannot provide similar reinforcing effects. In addition, the afterflame time of Example 1 is significantly shortened, showing a better flame retardant effect, which is due to the more effective flame retardant mechanism of magnesium hydroxide nanowires, which can decompose at high temperatures to generate water vapor, dilute the combustible gas in the combustion area and form a heat insulation layer. In Comparative Example 1, although the zinc oxide particles used have a certain flame retardant effect, they lack the synergistic effect of magnesium hydroxide nanowires, so the flame retardant effect is poor. Finally, the emissivity of Example 1 is relatively low, which shows that the addition of magnesium hydroxide nanowires not only enhances the structural properties of the material, but also contributes to the infrared shielding performance.

[0111] The main difference between Comparative Example 2 and Example 1 is that Comparative Example 2 uses magnesium hydroxide powder instead of magnesium hydroxide nanowires. As can be seen from Table 2, the magnesium hydroxide nanowires in Example 1 can significantly improve the tensile strength and elongation compared with magnesium hydroxide powder. This is because the nanoscale magnesium hydroxide can be more evenly distributed in the fiber matrix to form a better reinforced network structure, while the size of magnesium hydroxide powder is large and difficult to be evenly distributed, resulting in the reinforcement effect being inferior to that of nanowires. In addition, the LOI value of Example 1 is higher, indicating that the flame retardant effect of magnesium hydroxide nanowires is worse than that of magnesium hydroxide powder. This is because nanowires have a larger specific surface area and better dispersibility, and can more effectively capture and release moisture during combustion to form a denser thermal insulation layer. In terms of afterflame time, Example 1 is also significantly shortened, further illustrating that the flame retardant effect of nanowires is more significant. The decreasing trend of emissivity shows that nanowires also have a positive effect on infrared shielding performance, while the effect of magnesium hydroxide powder is relatively weak.

[0112] The main difference between Comparative Example 3 and Example 1 is that the polyimide composite fiber in Comparative Example 3 has not been surface-modified with basic zinc carbonate. As can be seen from Table 2, the polyimide composite fiber surface-modified with basic zinc carbonate in Example 1 can significantly improve the tensile strength and elongation. This is because the surface modification treatment enhances the interfacial bonding between the fiber and the matrix, thereby improving the overall mechanical properties. In Comparative Example 3, the interfacial bonding between the fiber that has not been surface-modified and the matrix is ​​weak, resulting in a decrease in mechanical properties. In terms of flame retardant properties, the LOI value of Example 1 is higher, indicating that the surface modification treatment is helpful in improving the heat resistance and combustion resistance of the fiber. The presence of basic zinc carbonate may form a protective oxide layer at high temperatures, further improving the flame retardancy. In terms of afterflame time, the performance of Example 1 is better than that of Comparative Example 3, further illustrating the advantages of surface-modified fibers in flame retardancy, and the effect on emissivity is relatively small.

[0113] The main difference between Comparative Example 4 and Example 1 is that the polyimide composite fiber in Comparative Example 4 uses graphene oxide that has not been surface-modified with dopamine. As can be seen from Table 2, the use of graphene oxide surface-modified with dopamine in Example 1 significantly improves the tensile strength and elongation of the fabric. This is because the dopamine modification treatment can enhance the interface bonding between graphene oxide and the polyimide matrix, forming a more uniform fiber structure, thereby improving the mechanical properties of the fiber. In Comparative Example 4, the binding force between the unmodified graphene oxide and the matrix is ​​weak, and there is a lack of interfacial synergistic enhancement effect. In terms of flame retardant properties, the LOI value of Example 1 is higher, and the graphene oxide modified with dopamine can form a more effective protective layer at high temperatures, further improving the flame retardant effect. The shortening of the afterflame time also shows that the flame retardant properties of the modified graphene are better than those of the unmodified graphene. In terms of emissivity, the performance of Example 1 is significantly better than that of Comparative Example 4. The surface-modified graphene can better disperse and reflect infrared radiation, thereby improving infrared shielding performance.

[0114] The main difference between Comparative Example 5 and Example 1 is that polyethylene glycol is not added in Comparative Example 5. As can be seen from Table 2, the addition of polyethylene glycol in Example 1 can significantly improve the tensile strength and elongation, because polyethylene glycol can act as a plasticizer, improve the flexibility and ductility of the fiber, and thus improve the mechanical properties. In Comparative Example 5, due to the lack of plasticizing effect of polyethylene glycol, the flexibility of the fiber is poor, resulting in a decrease in tensile strength and elongation. In terms of flame retardant properties, the LOI value of Example 1 is higher, which may be because the presence of polyethylene glycol helps to form a more uniform carbonization layer and phase change heat absorption during the combustion process, thereby improving the flame retardant effect. The shortening of the afterflame time also shows that the presence of polyethylene glycol helps to improve the flame retardancy of the fiber. However, in terms of emissivity, Example 1 performs better than Comparative Example 5. The presence of polyethylene glycol may improve the dispersion effect of the surface-modified graphene, thereby enhancing the infrared shielding performance.

[0115] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.

Claims

1. A flame retardant fabric with infrared shielding performance, characterized in that: The yarns are obtained by weaving as warp yarns and weft yarns respectively, and the yarns are obtained by blending polyester composite fibers and surface-modified polyimide composite fibers; The polyester composite fiber is prepared from the following components in parts by mass: 4.0-8.0 parts of magnesium hydroxide / zinc oxide composite filler, 50-90 parts of polyester chips, 0.5-2.5 parts of polyethylene glycol and 0.4-1.2 parts of phthalate; The magnesium hydroxide / zinc oxide composite filler is composed of zinc oxide particles and magnesium hydroxide nanowires uniformly loaded on the surface of the zinc oxide particles; The surface-modified polyimide composite fiber is prepared by surface-modifying the polyimide composite fiber with basic zinc carbonate; The polyimide composite fiber is prepared from the following components in parts by mass: 0.5-3.5 parts of surface-modified graphene, 1.5-4.0 parts of polyethylene glycol, 40-60 parts of 4,4'-diaminodiphenyl ether, 36-54 parts of pyromellitic dianhydride, and 100-250 parts of N,N-dimethylformamide; The surface-modified graphene is obtained by surface-modifying graphene oxide with dopamine; The preparation method of the magnesium hydroxide / zinc oxide composite filler is as follows: by weight, 20-45 parts of zinc oxide particles, 3.5-8.0 parts of magnesium chloride, 1.5-3.5 parts of magnesium oxide and 50 parts of deionized water are mixed evenly, and then added into a Teflon-lined high-pressure reactor, and the mixture is kept warm at 150-170°C for 6-10 hours. After the reaction is completed, a white precipitate is collected by filtration, and then the white precipitate is washed with deionized water for 3 times. Subsequently, the washed white precipitate, 3.0-6.0 parts of sodium hydroxide and 80 parts of anhydrous ethanol are added into a stainless steel high-pressure reactor, and the mixture is kept warm at 110-130°C for 5-9 hours. After filtration, solid powder is collected, and then the mixture is washed with deionized water for 3 times. Finally, the mixture is dried in a vacuum drying oven at room temperature to a constant weight to obtain the magnesium hydroxide / zinc oxide composite filler.

2. A flame retardant fabric with infrared shielding performance as claimed in claim 1, characterized in that: The mass ratio of magnesium hydroxide to zinc oxide is (5-15):(95-85); The average diameter of the magnesium hydroxide nanowires is 35-70 nm, the average length is 100-350 nm, and the average particle size of the zinc oxide particles is 400-2000 nm.

3. The flame-retardant fabric with infrared shielding performance as claimed in claim 1, characterized in that: The preparation method of the polyester composite fiber is as follows: magnesium hydroxide / zinc oxide composite filler, polyester chips, polyethylene glycol and phthalate are mixed evenly, added into a twin-screw extruder, melt blended, then extruded, and fibers are sprayed out through a spinneret, and the polyester composite fiber is obtained after cooling.

4. A flame retardant fabric with infrared shielding performance as claimed in claim 3, characterized in that: The screw length-to-diameter ratio of the twin-screw extruder is (25-40):1; The extrusion temperature of the twin-screw extruder is 240-280°C.

5. The flame-retardant fabric with infrared shielding performance as claimed in claim 1, characterized in that: The preparation method of the surface modified polyimide composite fiber is as follows: after 2.5 to 5.5 parts of basic zinc carbonate and 100 parts of 5wt.% sodium hydroxide solution are mixed evenly by weight, the polyimide composite fiber is completely immersed in the mixed solution, the immersion time is 30 to 60 minutes, the immersion temperature is 60 to 80°C, and after the immersion is completed, it is washed with deionized water for 3 times, and finally dried at room temperature to completely obtain the surface modified polyimide composite fiber.

6. A flame retardant fabric with infrared shielding properties as claimed in claim 1 or 5, characterized in that: The preparation method of the polyimide composite fiber is as follows: surface modified graphene, polyethylene glycol and N,N-dimethylformamide are mixed and then ultrasonicated for 30 to 45 minutes to obtain a uniformly dispersed suspension, then the suspension is added to a reactor, and 4,4'-diaminodiphenyl ether and pyromellitic anhydride are continuously added under a nitrogen atmosphere, and polycondensation is carried out under stirring at 5 to 25°C for 10 to 15 hours, and a polyamic acid mixed solution is obtained after the reaction is completed, and a vacuum degassing treatment is performed after solution spinning to obtain polyamic acid primary fibers, and then the polyamic acid primary fibers are subjected to thermal imidization and heat setting stretching treatment at 300 to 550°C for 30 to 60 minutes, and the polyimide composite fibers are obtained after cooling; The mass ratio of the 4,4'-diaminodiphenyl ether to pyromellitic dianhydride is 1:0.

9.

7. A flame retardant fabric with infrared shielding properties as claimed in claim 6, characterized in that: The preparation method of the surface modified graphene is as follows: by weight, 0.5-2.5 parts of graphene oxide are added to 100 parts of ionized water, and after stirring evenly, 0.05-0.09 parts of dopamine are added, and then the pH is adjusted to 8.0-10.0 with ammonia water, and the reaction is continuously stirred at room temperature for 6-12 minutes. After the stirring is completed, the mixed solution is centrifuged to collect solid precipitates, and then the precipitates are washed once with deionized water, and finally dried in a vacuum drying oven at room temperature to constant weight to obtain the surface modified graphene.

8. The flame-retardant fabric with infrared shielding performance as claimed in claim 1, characterized in that: The average diameters of the polyimide composite fiber and the surface-modified polyimide composite fiber are 8-15 μm and 6-12 μm respectively; The mass ratio of the polyimide composite fiber to the surface-modified polyimide composite fiber in the yarn is (30-50):(70-50); The warp yarn weaving density of the yarn is 30-60 yarns / cm, and the weft yarn weaving density is 25-50 yarns / cm.

9. A method for preparing a flame-retardant fabric with infrared shielding performance according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Preparation of fibers: According to a formula, a polyester composite fiber and a surface-modified polyimide composite fiber are prepared respectively, wherein the polyester composite fiber is prepared by melt-blending a magnesium hydroxide / zinc oxide composite filler, a polyester chip, polyethylene glycol and a phthalate and then extruding and spinning the mixture, and the surface-modified polyimide composite fiber is prepared by surface-modifying the polyimide composite fiber with basic zinc carbonate; S2. Preparation of yarn: The polyester composite fiber and the surface-modified polyimide composite fiber prepared in S1 are blended in a mass ratio, and the blended fiber is spun into yarn using conventional spinning equipment; S3. Fabric preparation: The yarns prepared in S2 are used as warp and weft yarns, respectively, and a fabric is prepared by a weaving process according to the textile density; S4. Packaging and storage: The fabric prepared in S3 is cut, rolled and packaged. The packaged fabric is stored in a dry and ventilated environment, avoiding direct sunlight and moisture to ensure stable fabric performance.

Citation Information

Patent Citations

  • Fabric surface flame-retardant functional layer, preparation method thereof and flame-retardant fabric

    CN118048784A

  • Graphene polyimide composite fiber and preparation method thereof

    CN113737310A

  • Preparation method of magnesium hydroxide coated zinc oxide composite powder

    CN113929970A

  • Flame-retardant, anti-dripping, antibacterial and warm polyimide flame-retardant polyester blended fabric and preparation method thereof

    CN115386999A